IMPLEMENTASI PEMBELAJARAN BERBASIS CERITA UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA SEKOLAH DASAR - Kiki, Kiki (Jurnal Sultra Elementary School, 2023)
Story based learning has been proven effective in improving students' listening skills, particularly at the elementary school level. This article presents a literature review on the implementation of this method, focusing on theories, implementation strategies, and its impact on developing listening skills. The findings show that story-based learning not only enhances listening skills but also stimulates creativity, imagination, and student engagement in learning. This article is expected to serve as a reference for educators seeking to develop listening strategies through an engaging and relevant approach.